The Oral Microbiome in Oral Frailty and Healthy Ageing: A Narrative Review - Felisha Febriane Balafif; Anggun Rafisa; Faisal Kuswandani; Nuroh Najmi (Sean Institute, 2026)
The oral microbiome plays a fundamental role in maintaining oral and systemic health throughout the ageing process. Age-related physiological changes, oral frailty, and physical inactivity contribute to microbial dysbiosis, which has been associated with periodontal disease, chronic inflammation, and frailty. However, the relationship between exercise, oral microbial ecology, and oral frailty has not been comprehensively synthesized. This narrative review aimed to summarize current evidence regarding the oral microbiome and to explore its relationship with oral frailty and healthy ageing. A narrative review was conducted using articles published between 2021 and 2026. Five original studies investigating oral microbiome composition, physical activity, oral frailty, ageing, and systemic inflammation in older adults were critically reviewed and synthesized to identify common findings and emerging biological mechanisms. The reviewed evidence consistently demonstrated that regular physical activity, including moderate-intensity continuous training and high-intensity interval training, promotes beneficial alterations in oral microbial composition by increasing microbial diversity and reducing the abundance of opportunistic pathogens. Conversely, physical inactivity and oral frailty were associated with reduced microbial diversity. Current evidence supports a close interaction between physical activity, oral microbiome composition, oral frailty, and healthy ageing. Regular exercise appears to preserve oral microbial homeostasis while reducing inflammation and frailty-related microbial alterations. These findings highlight the oral microbiome as a promising biomarker and potential therapeutic target for promoting healthy ageing. Nevertheless, further longitudinal studies integrating metagenomics, host immune responses, and clinical oral outcomes are required to clarify the causal mechanisms underlying these interactions.